PECULIARITIES OF CONDUCTING LEGAL DEEDS ON THE INTERNET - Mostova, Galina (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of this article is to analyze the legislation of Ukraine, which regulates the conclusion of transactions on the Internet, domestic scientific works on this issue, as well as the experience of foreign countries in order to find ways to improve the national legislation that regulates the specified institution of law. The methodological basis of the research is general scientific and special methods of scientific knowledge. The use of these methods made it possible to identify and describe the peculiarities of concluding transactions on the Internet. Results: the current legislation of Ukraine lacks an unambiguous definition of an electronic contract regarding its classification as a written transaction or a separate type of transaction. Therefore, it is considered appropriate to classify electronic contracts as written types of transactions, as defined in the Civil Code of Ukraine, and to bring other legal acts regulating the institution of electronic contracts into compliance with civil legislation. At the same time, clear requirements for electronic contracts should be legislated, based on international experience. Discussion: the Model Law on Electronic Commerce of 1996 and the UN Convention on the Use of Electronic Communications in International Treaties of 2005 separately define: a) the conditions under which an electronic document can be legally equivalent to a written document; b) conditions under which an electronic document can be considered signed; c) the conditions under which an electronic document is equated to an original document. Similar requirements should be applied to electronic contracts and included in the current Civil Code of Ukraine and other legal acts that regulate the institution of electronic contracts. Different forms of offer and acceptance are also considered. It was emphasized that clear and unambiguous requirements regarding the form of the offer and acceptance are crucial for the validity of the electronic transaction.